2010
DOI: 10.4103/0970-9290.66625
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical evaluation in human saliva with special reference to ovulation detection

Abstract: This study concluded that saliva-specific carbohydrates in the ovulatory saliva make the possibility to develop a biomarker for detection of ovulation by non-invasive methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Alagendran et al ., (2009)[11] in their study to assess the usefulness of saliva as a biomarker of ovulation detection showed that saliva can be used to test cholesterol and phospholipids instead of blood. The present study also suggests that saliva may be used for TC, TGL, HDLC, VLDLC and to some extent for LDLC monitoring, as these follow the course of plasma lipid profile and show a positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Alagendran et al ., (2009)[11] in their study to assess the usefulness of saliva as a biomarker of ovulation detection showed that saliva can be used to test cholesterol and phospholipids instead of blood. The present study also suggests that saliva may be used for TC, TGL, HDLC, VLDLC and to some extent for LDLC monitoring, as these follow the course of plasma lipid profile and show a positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Female orangutans have a menstrual cycle which lasts for around 27–28 days [ 3 , 7 ] as in humans [ 8 ]. In women, the fertile period occurs circa 5–6 days before and during ovulation [ 9 ], which occurs around the 13 th or 14 th day of the cycle [ 10 ] similar as in orangutans [ 11 ]. The menstrual cycle of orangutan female can be sometimes monitored by visible menstruation.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization of body fluids, related to menstrual cycle, was first observed in human cervical mucus 60 years ago [ 16 ]. Saliva crystallization was later also described in humans in association with the fertile period [ 10 , 17 19 ] and pregnancy detection [ 20 ]. Saliva crystallization changes during the menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations